Comparison of Suture-Augmented Ligamentplasty to Transarticular Screws in a Lisfranc Cadaveric Model. (June 2020) - Nery, Caio; Baumfeld, Daniel; Baumfeld, Tiago; Prado, Marcelo; Giza, Eric; Wagner, Pablo; Wagner, Emilio
Background: Lisfranc injuries represent a spectrum of trauma from high-energy lesions, with significant instability of the midfoot, to low-energy lesions, with subtle subluxations or instability without gross displacement. Recently, treatment options that allow for physiologic fixation of this multiplanar joint are being evaluated. The purpose of this study was to analyze the stability of a cadaveric Lisfranc injury model fixed with a novel suture-augmented neoligamentplasty in comparison with a traditional transarticular screw fixation construct. Methods: Twenty-four fresh-frozen, matched cadaveric leg and foot specimens (12 individuals younger than 65 years of age) were used for this study. Two different types of Lisfranc ligament injuries were tested: partial and complete. Two different methods of fixation were compared: transarticular screws and augmented suture ligamentplasty with FiberTape. Specimens were fixed to a rotation platform in order to stress the joints while applying 400 N of axial load and internal and external rotation. Six distances were measured and compared between the intact, injured, and fixed states with a 3D Digitizer arm, in order to evaluate the stability between them. Analysis of variance was used with P < .05 considered significant. Results: Using distribution graphs and analyzing the grouped data, it was observed that there was no difference between the 2 stabilization methods, but the augmented suture ligamentplasty presented lower variability and observed distance shortenings were more likely to be around the mean. The variability of the stabilization with screws was 2.9 times higher than that with tape ( P < .001). Conclusion: We suggest that augmented suture ligamentplasty can achieve similar stability to classic transarticular screws, with less variability. Clinical Relevance: This cadaveric study adds new information on the debate about Lisfranc lesions treatment. Flexible fixations, such as the synthethic ligamentplasty used, can restore good stability such as conventional transarticular screws.